Zapisz wyrażenie w najprostszej postaci, a następnie oblicz jego wartość liczbową
4x-(x-6)+4 dla x 1/3
(-a2+2ab-1)+(a2-4ab+5) dla a -1/4 dla b -2



Odpowiedź :

Odpowiedź:

4 * 1/3 - ( 1/3 - 6) +4 = 4/3 - (-14/3) + 4 =4/3 + 14/3 + 4 = 18/3 + 4 = 10

(- (-1/4)2 + 2 * (-1/4) * - 2 - 1) + ( (-1/4)2 - 4 * (-1/4) * (-2) + 5 = 1/2 + 1/2 * (-3) + (-1/2) + 1 * (-2) + 5 = - 3 + (-1/2) - 2 + 5 = - 1/2

Odpowiedź:

4x-(x-6)+4 dla x =1/3

4x-x+6+4=

3x+10

[tex]3*\frac{1}{3}+10=\frac{3}{3}+10=1+10=11[/tex]

(-a²+2ab-1)+(a²-4ab+5) dla a =-1/4 dla b= -2

(-a²+2ab-1)+(a²-4ab+5)=

-a²+2ab-1+a²-4ab+5=

-2ab+4

[tex]-2*(-\frac{1}{4})*(-2)+4=-\frac{4}{4}+4=-1+4=3[/tex]

Szczegółowe wyjaśnienie: